True cost accounting : assessing environmental and social damages of production - Michalke, Amelie; Kunz, Jennifer; Gaugler, Tobias (Routledge, Taylor & Francis Group, 2025)
This book explores the historical and theoretical classification of True Cost Accounting (TCA) and its business-oriented ways of implementation.Tobias Gaugler, Jennifer Kunz, and Amelie Michalke provide compact and comprehensible insights into TCA, which is one approach used to comprehensively assess actual (human or natural) resource consumption and implement this assessment into companies' internal controlling. To achieve this goal, the volume locates this approach in existing economic theory and shows its historical roots and progressions. The authors then present different methodological approaches within TCA and highlight how practitioners might implement these approaches in their business. To illustrate the importance of TCA, a number of practical examples that are already present in the market are also featured.This volume will be of great interest to students and scholars of environmental economics. Further, practitioners in (sustainable) supply chain management, as well as ecological and social accounting and controlling, can use it for inspiration and guidance. Additionally, this book and the inherent ideas will give policymakers in economic and social politics recommendations for action.
Keywords: Accounting.; Environmental policy.; Environmental Cost Accounting; Social Cost Accounting; Sustainable Supply Chain Management; Value Chain; Sustainable Consumption; Sustainable Production; Social Equity; Environmental Justice; elektronické knihy; electronic books